New Findings on Racial Bias in Teachers' Evaluations of Student Achievement - Maria Zhu (Institute of Labor Economics (IZA), 2024)
This paper examines racial discrepancies in teachers' evaluations of student achievement, conditional on standardized test achievement. After correcting for measurement error in standardized test scores, results indicate teachers evaluate Black students as higher achieving than White students with the same standardized test achievement. This finding stands in contrast to prior findings on Black-White teacher assessment gaps. Further analysis indicates these findings are consistent with two potential explanations: first, standardized tests may exhibit bias against Black students, and second, teachers may inflate assessments of Black students relative to White students due to social desirability bias.
Keywords: I20; J15; 330; teacher assessments; racial bias; standardized tests